철도종사자의 사회 재난 적응 경험 : 1977년 이리역 폭발 사고를 중심으로 - 정호기; 양야기 (한국직업건강간호학회지, 2019)
Purpose: The Iri station explosion that occurred in 1977 was a major social disaster in Korea, caused by a fire in a train equipped with explosives. The purpose of this study was to investigate the social disaster adaptation experiences of railroad workers. Methods: This study was based on qualitative research using phenomenological methodology. Participants were six railroad workers who experienced the Iri station explosion. Data were collected through in-depth interviews with individual workers from March to June, 2018. The data analysis method was based on Colaizzi’s approach. Results: Experiences of railroad workers were categorized into 12 themes and the following 6 theme clusters: (1) Anxiety due to the extreme vibration and crash, (2) Terror regarding the horrible situation that one cannot face, (3) Anger about the cause of the explosion and a sense of relief about survival, (4) Confusion regarding different rumors, (5) Various efforts to return to daily life, and (6) Trauma that continues to exist. Conclusion: The findings of this study recommend that railroad organizations and managers should pay attention to enhance disaster preparedness and develop organizational disaster coping guidelines for members. The results of this study can help us to better understand the various aspects of the Iri station explosion of 1977.